Perspective taking in language: When bodily involvement impacts motion events’ descriptions (Signifiances (Signifying), 2017)
Relying on the Talmian typology, this investigation explores perspective taking in language through English and French spoken corpora delivered by speakers submitted to different bodily constraints before delineating motion events. The effects of speakers’ bodily involvement on their linguistic identification of perspectives are spotlighted, relying on the hypothesis according to which speakers’ sensorimotor processes can be corollary mirrored in their speech acts. Descriptions are analysed through the concept of embodiment, which highlights the significant role played by the body through speakers’ reports. Language users are apprehended as enacting the world through linguistic productions resulting from bodily, linguistic and non-linguistic variables. Identification langagière de la perspective:L’incidence de contraintes corporelles sur la description du mouvement Fondée sur la typologie talmienne, cette étude examine l’identification langagière de la perspective au travers de corpus oraux français et anglais, issus de locuteurs soumis à différentes contraintes corporelles initiant leur description du phénomène de mouvement. On souligne l’effet de l’implication sensorielle des locuteurs sur les perspectives adoptées dans leur discours, à partir de l’hypothèse selon laquelle les processus sensorimoteurs des sujets parlants sont reflétés dans leurs productions langagières. Les corpus sont analysés au travers du concept d’embodiment (ou corporéité), considérant ici l’inscription significative du corps dans les propos recueillis. On appréhende les locuteurs comme des sujets qui énactent le monde au travers de productions langagières – réceptacles de paramètres corporels et de variables verbales et non verbales.
Keywords: Motion; Perspective; Sensorimotor processes; Embodiment; Enaction // Mouvement; Processus sensorimoteurs; Corporéité; Enaction